Influence of co-blending fly ash and ceramic waste powder on the performance and microstructure of cementitious substrates under sulfate dry-wet cycle attack - Xinyan Wang; Lu Zhang; Haizhou Li (PLoS ONE, 2025)
This study examines the properties of cement-based materials incorporating composite additions of fly ash and ceramic waste powder (CWP) as supplementary cementitious materials (SCM). The resistance of the materials to sulfate erosion under dry-wet cycling conditions was investigated through experimental testing. A Box-Behnken Design was employed to establish a model using three factors: the replacement ratio of cement by SCMs, the mass ratio of CWP to SCMs, and the water-to-binder ratio. The response variable was the mass loss rate due to sulfate erosion after 24 cycles of dry-wet cycling. Significance analysis of single-factor and multiple-factor interactions was conducted based on the response surface model. The research findings indicate that the cement-based materials with combined additions of fly ash and CWP exhibit optimal resistance to sulfate erosion under dry-wet cycling conditions. The water-to-binder ratio was identified as the most significant factor affecting the corrosion resistance of the cement-based materials at 7 days of curing. The dosage of ceramic waste powder influenced the corrosion performance of the cement-based materials at 28 days of curing. The content of SCMs affected the corrosion resistance of the cement-based materials after 56 days of curing. Comparative analysis of the grayscale three-dimensional distribution map and histogram of the cement-based materials with SCMs revealed an increase in the compactness of the matrix.